High dilution preparations for organic production system of broccoli (2017)
The aim of this study was to evaluate the influence of high dilution preparations on seedlings growth and production of broccoli under organic system. Three experiments were conducted in a greenhouse with completely randomized design. Two others experiments were conducted under field conditions, and the experimental design was randomized in blocks. Both designs were done with four replications and nine treatments. The treatments consisted of high dilution preparations of Arnica montana, Silicea terra, Carbo vegetabilis and Sulphur at 6CH or 30CH, water was used as control. In greenhouse, plant height, root length and stem diameter of seedlings were evaluated, along with the fresh and dry mass of shoot and root. In field, fresh and dry mass of inflorescences, plant heigh and stem diameter were evaluated. Silicea terra at 30CH increased the stem diameter, root length and dry mass of shoot and root in the broccoli seedlings. Sulphur at 6CH increased the fresh and dry mass of broccoli inflorescences. Silicea terra at 6CH, Carbo vegetabilis, and Sulphur at 30CH increased the plant height in field experiments. This suggests that high dilution preparations can be utilized to increase the biomass production and others desirable characteristics of broccoli crop under organic system.